Perancangan Aplikasi Marketplace Petani Saribu Dolok Hangoluan Medan - Purba, Bagas Andika Cristo; Perangin-angin , Resianta; Saragih, Rijois I. E. (Universitas Methodist Indonesia, 2024)
Agriculture is an activity carried out by humans to produce food or energy sources to manage their environment. In today's development, information technology has increased rapidly in various fields. As in the field of agriculture, information technology also provides many benefits to the community, especially the Garingging farmer group. The problem that occurs with the Garingging farmer group is that there is no application that helps farmer groups in selling agricultural products without going through intermediaries so that farmers selling agricultural products get unsatisfactory prices. The solution taken to solve this problem is to build a marketplace application design to make it easier for farmer groups to sell their agricultural products using several programming applications. The results of the research that has been carried out and the website that has been built is to help farmer groups sell their agricultural products easily so that farmer groups sell agricultural products not through intermediaries but through sellers and buyers in order to get satisfactory prices for farmers.